COLLABORATIVE STRATEGIC READING EFFECT ON READING COMPREHENSION BY CONSIDERING LEARNERS’ COGNITIVE STYLES - Leroy Holman Siahaan; Aceng Rahmat; Nuruddin Nuruddin (University of Kuningan, 2022)
The use of collaborative tactics based on Moodle is quite effective in assisting students in improving their reading comprehension. Moodle is an online education platform that creates a unique learning environment for students to learn in. Students are split into two groups based on their attitudes toward information from outside sources: field-independent learners and field-dependent learners. The Independent Learner has a self-sufficient mentality and is not depending on others. The dependent learner, on the other hand, is a student who is completely reliant on the people or her immediate surroundings. The goal of this research is to see how collaborative techniques based on Moodle and Cognitive Styles affect students' reading comprehension. It divides the participants into two groups at random: an experimental group that received CSR through Moodle, and a control group that received CSR without Moodle. The GEFT (Group Embedded Figures Test) is used to see if the participants' cognitive styles are field-independent or field-dependent. Furthermore, a two-way ANOVA and descriptive test are used to analyze the data. The results of ANOVA test revealed that the learners' reading comprehension was influenced by CSR and cognitive styles. This study suggests that English teachers use Moodle for CSR with cognitive types to help students improve their reading comprehension. Finally, the descriptive test's average differences revealed that CSR with Moodle is better for learners with independent cognitive styles than for those with dependent ones. CSR without Moodle, on the other hand, is best for dependent learners.